2008
DOI: 10.1007/s11596-008-0604-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betulinic acid on proliferation and apoptosis in Jurkat cells and its in vitro mechanism

Abstract: The anti-cancer effects of betulinic acid (BA) on Jurkat cells and its in vitro mechanism were examined by using MTT assay. Apoptosis was detected by using Hoechst33258 staining and annexin-V/PI double-labeled cytometry. The effects of betulinic acid on the cell cycle of Jurkat cells were studied by propidium iodide method. RT-PCR and Western blotting were used to analyze the changes of cyclin D3, bcl-xl mRNA and protein levels in Jurkat cells after treatment with betulinic acid. Our results showed the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Cyclin D3 was found to be sharply decreased in Jurkat cells treated with BetA and the same study also found that BetA regulates the cell cycle through the induction of G 0 /G 1 arrest, thereby inhibiting proliferation [106]. Another group found accumulation of p21 on BetA exposure in glioma cells.…”
Section: Cell Cyclementioning
confidence: 72%
“…Cyclin D3 was found to be sharply decreased in Jurkat cells treated with BetA and the same study also found that BetA regulates the cell cycle through the induction of G 0 /G 1 arrest, thereby inhibiting proliferation [106]. Another group found accumulation of p21 on BetA exposure in glioma cells.…”
Section: Cell Cyclementioning
confidence: 72%
“…BA also down regulates the expression of STAT3-regulated gene products such as Bcl-xL, Bcl-2, cyclin D1 and survivin, which correlates with an increase in apoptosis as indicated by an increase in the sub-G1 cell population and an increase in caspase-3-induced PARP cleavage [12]. The antitumor effects of BA are related to the downregulation of cycli D and Bcl-xL expressions [13]. Studies have demonstrated that BA shows antimetastatic effects by inhibiting epithelial mesenchymal transition (EMT) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we showed that these properties are enhanced in BA5 derivative. In fact, the antiproliferative effect of BA and other terpenoids is well recognized in different tumor cell lines, especially in leukemia lineages, such as Jurkat cells, in which BA treatment induced cell cycle arrest in pre-G1 phase followed by cell death by apoptosis (Chen et al, 2008). Interestingly, a similar pathway of cell death was observed in lymphocytes treated with BA5.…”
Section: Discussionmentioning
confidence: 89%